2000
DOI: 10.1073/pnas.97.21.11371
|View full text |Cite
|
Sign up to set email alerts
|

The expression of adipogenic genes is decreased in obesity and diabetes mellitus

Abstract: Obesity is strongly correlated with type 2 diabetes mellitus, a common disorder of glucose and lipid metabolism. Although adipocytes are critical in obesity, their role in diabetes has only recently been appreciated. We conducted studies by using DNA microarrays to identify differences in gene expression in adipose tissue from lean, obese, and obese-diabetic mice. The expression level of over 11,000 transcripts was analyzed, and 214 transcripts showed significant differences between lean and obese mice. Surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
239
5
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(282 citation statements)
references
References 42 publications
36
239
5
2
Order By: Relevance
“…Recently, Moraes et al (2003) reported, using oligonucleotide micro-array analysis, that approximately 500 genes were differentially expressed in adipose tissue of DIO-C57BL/6J mice. Interestingly, genes coding markers for adipocyte differentiation are down-regulated whereas there is no variation in the expression of the main adipogenic transcription factors, contrasting with the results obtained with adipose tissue from leptin-deficient obese ob/ob mice (Nadler et al, 2000). This latter observation shows that the gene expression profile in adipose tissue of genetic models of obesity, such as the ob/ob mice, does not reflect the profile obtained with obesity induced by overfeeding, reinforcing the interest of these rodent models of diet-induced obesity.…”
Section: I3 Adipose Tissue and Calorie Restrictioncontrasting
confidence: 89%
“…Recently, Moraes et al (2003) reported, using oligonucleotide micro-array analysis, that approximately 500 genes were differentially expressed in adipose tissue of DIO-C57BL/6J mice. Interestingly, genes coding markers for adipocyte differentiation are down-regulated whereas there is no variation in the expression of the main adipogenic transcription factors, contrasting with the results obtained with adipose tissue from leptin-deficient obese ob/ob mice (Nadler et al, 2000). This latter observation shows that the gene expression profile in adipose tissue of genetic models of obesity, such as the ob/ob mice, does not reflect the profile obtained with obesity induced by overfeeding, reinforcing the interest of these rodent models of diet-induced obesity.…”
Section: I3 Adipose Tissue and Calorie Restrictioncontrasting
confidence: 89%
“…On the other hand, the adipocytes of obese subjects had decreased expression of genes encoding energy pathway/electron transport. The overall gene expression profile of these isolated human adipocytes is similar to that of the adipose tissue of dietinduced obese C57BL/6J mice [14] and that of genetically obese (ob/ob) mice with a mutation in the gene encoding leptin on different strain backgrounds [9,12,13]. Further studies are required to investigate the relative contributions of genetic background and dietary intake to the differential adipocyte gene expression in obese people.…”
Section: Discussionmentioning
confidence: 85%
“…The role of adipose tissue in the aetiology of obesity [7], as well as its pathophysiological consequences [8], is increasingly being recognised. A few studies in rodents and humans have used microarray gene expression profiling of whole adipose tissue to investigate its role in obesity [9,10]. Unfortunately, the heterogeneous cell composition of adipose tissue does not provide information on the potentially diverse functions of the specific cell types of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses revealed that four such defined sets of genes were downregulated (p<0.05) in livers from HFD Il6 −/− compared with control mice. These included 'Nadler Obesity Hyperglycaemia' [29] (ESM Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…This defined gene set included genes involved in signal transduction and energy metabolism, as well as genes not previously examined in the context of diabetes. Nadler et al [29] demonstrated that a decrease in expression of this gene set was associated with obesity and hyperglycaemia. In addition, the other related sets of genes that were coordinately downregulated were genes associated with the tricarboxylic acid cycle (Fig.…”
Section: Resultsmentioning
confidence: 99%